Structural engineering of BiOBr nanosheets for boosted photodegradation performance toward rhodamine B. Issue 15 (22nd March 2022) - Qi, Yu; Zhao, Jinjiang; Wang, Hongtao; Yan, Meifang; Guo, Tianyu
Abstract : A series of BiOBr nanosheets were synthesized through a facile solvothermal method, whose structures were adjusted by changing solvent ratios. Abstract : A series of BiOBr nanosheets were synthesized through a facile solvothermal method, whose structures were adjusted by changing solvent ratios. Their photodegradation properties toward rhodamine B (RhB) were further investigated under visible light irradiation. The photocatalytic results indicated that the B-1:3 sample showed superior photoactivity and the RhB removal efficiency attained 97% within 30 min. The outstanding photodegradation activity can be ascribed to the small particle size and thickness, suppressed e − –h + pair recombination and more active electrons and holes. Moreover, free radical quenching experiments suggest that ·O2 − and h + play a crucial role in improving photoactivity. This work opens a new avenue to boost the removal rate of organic pollutants by engineering the solvent ratios of photocatalysts in the wastewater treatment field.